Dissecting intermolecular interactions in the condensed phase of ibuprofen and related compounds: the specific role and quantification of hydrogen bonding and dispersion forces. Issue 9 (13th January 2020) - Emel'yanenko, V. N.; Stange, P.; Feder-Kubis, J.; Verevkin, S. P.; Ludwig, R.
Abstract : Hydrogen bonding and dispersion interaction in liquid ibuprofen is analyzed by thermodynamic methods, infrared spectroscopy and quantum chemistry. Abstract : Ibuprofen is a well-established non-steroidal anti-inflammatory drug, inhibiting the prostaglandin-endoperoxide synthase. One of the key features defining the ibuprofen structure is the doubly intermolecular O–H⋯OC hydrogen bond in cyclic dimers as know from carboxylic acids and confirmed by X-ray analysis. Until now, there was neither information about the vaporization enthalpy of ibuprofen nor about how this thermal property is determined by the subtle balance between different types of intermolecular interaction. In this study we derive the vaporization enthalpy of ibuprofen from thermochemical experiments to be . We dissected the hydrogen bond energy, E HB = 45.0 kJ mol −1, exclusively from measured vaporization enthalpies of related aliphatic carboxylic acids, their homomorph methyl esters and alkyl acetates, respectively. This contribution from hydrogen bonding could be confirmed almost quantitatively from quantum chemical calculations of ibuprofen clusters, which also suggest dispersion interaction of similar order ( E disp = 47 kJ mol −1 ). Following the full analysis of the gas–vapor transition enthalpy, we studied the changing structural components from the solid to the liquid phase of ibuprofen by means of Attenuated Total Reflection Infrared (ATR-IR) spectroscopy. The cyclic dimers as observed in the X-ray patterns are essentially preserved in the liquid state just above the melting point. However, with increasing temperature the doubly hydrogen-bonded cyclic dimers are replaced by singly hydrogen-bonded linear dimers in the liquid ibuprofen. The transfer enthalpy from the temperature-dependent equilibria of both dimers as obtained from the IR intensity ratios of the vibrational bands quantifies for the first time the energy of the released, single hydrogen bond to be E HB = 21.0 kJ mol −1 . Overall, we show that a combination of thermodynamics, infrared spectroscopy and quantum chemistry provides quantification and detailed understanding of structure and molecular interaction in ibuprofen and related compounds.